Electrochemical Reactions of Aldehydes/Ketones at Sacrificial Nickel Anode: Synthesis and Characterization of Nickel(II) Glycolates and Their Coordination Complexes - Shavina; Singh, Baljit; Kaur, Satinderpal (Asian Journal of Chemistry, 2018)
Complexes of some aldehydes (acetaldehyde, propionaldehyde, butyraldehyde, cinnamaldehyde and benzaldehyde) and ketones (ethyl methyl ketone, isobutyl methyl ketone, acetophenone, benzophenone and p-chlorobenzophenone) have been synthesized at sacrificial nickel anode and inert platinum cathode using tetrabutylammonium chloride as supporting electrolyte. Characterization of compounds by vibrational spectroscopy, elemental analysis and physical measurements confirm that these compounds are unique polymeric nickel(II) glycolates of general formula {Ni(RR’CO)2}n. Refluxing of these glycolates with ligand (2,2’-bipyridyl or 1,10-phenanthroline) does not synthesize coordination compounds. However, the coordination complexes have been synthesized by electrolyzing the aldehyde/ketone in the presence of ligand in acetonitrile at sacrificial nickel anode. Current efficiency of all these systems has been determined in order to check the viability of these reactions on commercial scale.